Analisis Risiko Produksi Dan Pendapatan Usahatani Bawang Merah: (Studi Kasus Desa Panggih Kecamatan Trowulan Kabupaten Mojokerto) - Nur Farida Kusumawati (Media Agribisnis, 2023)
Shallots (Allium ascolonicum, L.) is a priority commodity in the development of lowland vegetables in Indonesia which is quite strategic and economical in terms of farming profits. Financially, this farming is quite profitable, on the other hand, onion farming has a fairly high level of risk, both business risk (fluctuating selling prices) and production risk. This study aims to 1. Analyze the production factors of shallots. 2. To analyze the production risk of shallot farming. 3. To analyze the income of onion farming. Analysis of the data used is quantitative data and qualitative data with the data sources used are primary data and secondary data. The analytical tools used are risk level analysis, income analysis. The results of the study show the risk of production and income in Panggih village, Trowulan district, Mojokerto district. Production risks faced by farmers are high prices for seeds, expensive and difficult fertilizers and pesticides with volatile selling prices of shallots, as well as unpredictable weather, pests and diseases, esecially fusarium, moller and armyworm. As for the risk analysis of shallot production from the coefficient of variation (CV) of 0.07, it means that if <0.50 then the farmer is always profitable, while the value is > 0.50 then the production risk of shallot farmers must accept the greater risk, and for the shallot income an average of IDR 16,964,303/season (2 months) Keywords: income, shallots, production risk